2018
DOI: 10.1007/s40430-018-1450-8
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of cutting forces and hole accuracy in reaming an Al–Si–Mg alloy (6351) with different copper contents

Abstract: The main purpose of this work is to study the influence of copper content on Al-Si-Mg aluminum alloy's (6351) machinability. This alloy's machinability was evaluated through cutting tool torque and thrust force measurements, holes' surface roughness, diameter, roundness, cylindricity and subsurface modifications during the reaming process. The Al-Si-Mg alloy samples were produced with five levels of copper (0.07%, 0.23%, 0.94%, 1.43% and 1.93%) and have a chemical composition of the other alloying elements pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…5. and holes on the machined surface, tool wear and so on (Yan et al 2013;Goncalves et al 2018). But we can see that numerical simulation and experimental results have the same trend: fatigue life increases with the increase of reaming depths, and the best fatigue gain effect of the specimen is obtained when the reaming depth of 0.5 mm.…”
Section: Fatigue Life Results and Experimental Verificationmentioning
confidence: 99%
“…5. and holes on the machined surface, tool wear and so on (Yan et al 2013;Goncalves et al 2018). But we can see that numerical simulation and experimental results have the same trend: fatigue life increases with the increase of reaming depths, and the best fatigue gain effect of the specimen is obtained when the reaming depth of 0.5 mm.…”
Section: Fatigue Life Results and Experimental Verificationmentioning
confidence: 99%
“…Cutting stability is considered as prerequisite in metal cutting to achieve good dimensional accuracy, surface quality, and tool life (Zhu et al, 2018). Gonçalves et al (2018) studied effect of cutting speed and feed on roundness and cylindricity in reaming of Al-Si-Mg alloy (6351). They concluded that stability of tool resulted in low tool vibration because of low stresses applied on the tool.…”
Section: Introductionmentioning
confidence: 99%